"الموضوعات المقارنة في كتاب رفاعة الطهطاوي "تخليص الإبريز في تلخيص باريز - Inyass Muhammad Mahdi
Rifa’ah Rafi At-Tahtawiy is considered one the prominent pioneers and pillars of the modern enlightenment and academic development in Egypt and Arab world during the nineteenth century. Indeed, he was delegated to France and the outcome of his delegation was the emergence of his publication titled “Talkhis al-Ibriz fi Talkhis Pariz” dealing with comparative themes. Thus, this research aims at bringing out those comparative subject matters; by explaining and extracting the literary themes, analysing linguistic issues and exploring some cultural and traditional matters. It, in other words, seeks to answer the following questions: what are the literary subject matters contained in his book? What are the linguistic issues found in it? What are the cultural and conventional subject matters contained? The researcher employed a descriptive analytical method for the explanation of the facts related to the topic in question. Then, among the outcomes of the research is that the book “Talkhis al-Ibriz” is considered one of the first books dealing with comparative subject matters in the Arab world not in an applied way; because it presented the comparative themes in the literary, linguistic, cultural and conventional aspects. In the end, the researcher suggests the need to give attention to comparative subject matters; in that they enhance linguistic aptitude and critical ability. Besides, they give room for a wide and deep exposure to the knowledge of bases of civilisation and development of different nations and people.